The Role of Religious Leaders Amid Conflict of Public Resistance to Industrial Activities in Gresik - Anas, Mohamad; Wulandari, Prisca Kiki; Saraswati, Destriana; Utami, Diah Febri (KARSA: Journal of Social and Islamic Culture, 2020)
The research constitutes an analysis on the conflict between community in Ujungpangkah, Gresik, East Java and a gas company, PT Aramada Hess (now PGN Saka Energy Indonesia). The research aims at finding a conflict resolution model that is distinctive, appropriate, and successful. To support the qualitative research, data collection methods use purposive sampling, participatory observation techniques, in-depth interviews and document reviews.Â  The collected data are analysed with the theory of mapping C.R. SIPPABIO. The theory under which the researcher applying to understand the role of Ujungpangkah religious leaders in resolving conflicts between the community and PGN Saka Energy Indonesia. As a result, it is found that: 1) public leaders are derived from various groups (fishermen, fishpond entrepreneurs and Islamic boarding school leaders) who positively resolve the conflict; 2) the intervention method is used as conflict resolution with a negotiation model; 3) Ujungpangkah religious leaders become social cohesion in this open conflict.